Analysis of the Influence of Quality of Education Services and Facilities and Infrastructure on the Trust of the Community of Boarding Boards Az - Ziyadah with Satisfaction as a Mediation Variable - Nurlaila; Guswandi; Subagja, Iwan Kurniawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to: 1) test and analyze the effect of Quality of Education Services and InfrastructureFacilities on Satisfaction, 2) test and analyze the effect of Quality of Educational Services CommunityTrust, 3) test and analyze the effect of Satisfaction on Public Trust, 4) test and analyze the effect ofQuality Education Services on Public Trust through Satisfaction, 5) test and analyze the influence ofInfrastructure on Public Trust through Satisfaction at the Az Ziyadah Islamic Boarding School, EastJakarta. The research was conducted at the Az Ziyadah Islamic Boarding School in East Jakarta with aresearch sample of 175 respondents. Sampling technique used is the Simple Random Sampling. Thedata analysis method used is path analysis. The results of the study show that: 1) There is an influenceof Quality Educational Services and Infrastructure Facilities on Satisfaction. 2) There is an influence ofthe Quality of Educational Services and Infrastructure Facilities on Public Trust. 3) There is an influenceof Satisfaction on Public Trust. 4) There is an influence of the Quality of Educational Services on PublicTrust through Satisfaction. 5) There is an influence of Infrastructure to Public Trust through Satisfactionat the Az Ziyadah Islamic Boarding School, East Jakarta.